2001
DOI: 10.1590/s1517-83822001000400014
|View full text |Cite
|
Sign up to set email alerts
|

Partial purification and characterization of exopolygalacturonase II and III of Penicillium frequentans

Abstract: Previous studies from our laboratory have demonstrated that the fungus Penicillium frequentans produces high levels of polygalacturonase and pectinesterase. Endopolygalacturonase I (Endo-PG I) and Exopolygalacturonase I (Exo-PG I) were previously purified and characterized. In the present study two extracellular polygalacturonases were separated, partially purified and biochemically characterized. Both were characterized as exopolygalacturonases so they were named exopolygalacturonase II (Exo-PG II) and exopol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…The K m values of most of the microbial PGs are in the range of 0.1-5.0 (Polizeli et al 1991;Zhang et al 1999;Niture et al 2001;Singh and Rao 2002;Thakur et al 2010a, b;Yadav et al 2012;Martins et al 2013;Chen et al 2014). An exo-PG from the fungus Penicillium frequentans has very low K m value of 0.059 (Barense et al 2001) while PG from pathogenic fungus Ustilago maydis revealed comparatively very high K m of 57.84 (Castruita-Domínguez et al 2014). The catalytic rate constant k cat of purified PG was found to be 194 s -1 which is higher than k cat values of 90 and 70 s -1 for endo-PGs from Aspergillus japonicus and Fusarium moniliforme (Semenova et al 2003;Niture et al 2001).…”
Section: Kinetic Parametersmentioning
confidence: 99%
“…The K m values of most of the microbial PGs are in the range of 0.1-5.0 (Polizeli et al 1991;Zhang et al 1999;Niture et al 2001;Singh and Rao 2002;Thakur et al 2010a, b;Yadav et al 2012;Martins et al 2013;Chen et al 2014). An exo-PG from the fungus Penicillium frequentans has very low K m value of 0.059 (Barense et al 2001) while PG from pathogenic fungus Ustilago maydis revealed comparatively very high K m of 57.84 (Castruita-Domínguez et al 2014). The catalytic rate constant k cat of purified PG was found to be 194 s -1 which is higher than k cat values of 90 and 70 s -1 for endo-PGs from Aspergillus japonicus and Fusarium moniliforme (Semenova et al 2003;Niture et al 2001).…”
Section: Kinetic Parametersmentioning
confidence: 99%
“…The molecular mass of the purified enzyme determined from SDS-PAGE analysis was 75.5 kDa. The molecular mass of purified fungal PGs reported in literature ranges from 25 kDa to 82 kDa (Barense et al 2001;Sakamoto et al 2002;Niture Fig. 3.…”
Section: Purification Of Pgmentioning
confidence: 99%
“…Various fungal species including Aspergillus niger, Aspergillus ustus, Aspergillus awamori Acuna-Arguelles et al 1995;Rao et al 1996;Blandino et al 2002), Botrytis cinerea (Schejter & Marcus 1988;Cabanne & Doneche 2002), Colletorichum lindemuthianum (English et al 1972;Herert et al 2004), Corticium rolfsii (Kaji & Okada 1969), Fusarium oxysporum f. sp. melonis (Martinez et al 1991), Fusarium moniliforme (Bonnin et al 2001;Niture et al 2001), Neurospora crassa (De Lourdes et al 1991), Penicillium frequentans (Barense et al 2001;dos Santos Cunha Chellegatti et al 2002), Rhizopus stolonifer (Manachini et al 1987), a non-pathogenic fungus Rhizoctonia AG-G (Machinandiarena et al 2005) and yeast strain Saccharomyces cerevisiae (Blanco et al 1994) produced either endo/exo or both PGs during the course of saprophytic growth or during plant pathogenesis. PGs are inducible enzymes (Nyiri 1968;Aguilar & Huitron 1987;Kawano et al 1999), however, constitutive PG expression was also reported in Botrytis cinerea ( Van der Cruyssen et al 1994).…”
Section: Regulation Of Fungal Pgs Productionmentioning
confidence: 99%